Factor Structure of the Shortened Six-Item Version of the de Jong Gierveld Loneliness Scale (DJGLS-6). A Systematic Review and Testing Factor Models in a Nationally Representative Sample (European Journal of Mental Health, 2023)
Introduction: Loneliness is linked to negative physical and mental health outcomes. Therefore, it is important to employ reliable and valid screening measures for early detection and treatment. A widely used scale for assessing loneliness is the shortened six-item Jong Gierveld Loneliness Scale (DJGLS-6).Aims: To review and evaluate the factor structure of the DJGLS-6.Methods: Study 1 was a systematic review. To examine the factor structure of the DJGLS-6, peer-reviewed studies were reviewed in accordance with PRISMA guidelines. Study 2 tested the factor analytic models found in Study 1. Confirmatory factor analysis (CFA) was performed using data from a nationally representative sample of adults to assess the latent structure of the six-item scale.Results: In Study 1, findings from the two papers reviewed suggested that the scale measures two correlated dimensions: social and emotional loneliness. This finding was consistent with the results of Study 2. However, the fit statistics for the one and two-factor CFA models were not acceptable. Modification indices indicated that adding a cross-factor loading to allow item 2 (“I miss having people around”) of the social loneliness factor, to load on both the emotional and social factor, to load on both the emotional and social factors would significantly improve the fit of the model.Conclusions: The analysis failed to support previous findings concerning the robustness of the subscales. We recommend performing future evaluations of the scale and for the authors to consider changing item 2 accordingly.